Mengukur Tingkat Kematangan Penggunaan Sumber Daya Sistem Informasi Pada Rumah Sakit - Friska Aryani; Hasmawaty Hasmawaty; Widya Cholil (Jurnal Pengembangan Sistem Informasi dan Informatika, 2020)
The information system is very important in operational activities at RSIA Hamami. The purpose of evaluating the use of information system resources at RSIA Hamami is to measure the performance of the information system with the services provided by RSIA Hamami. The method used in evaluating is COBIT 5.0, the method used is descriptive quantitative with a research instrument in the form of a questionnaire. The focus in this study uses several COBIT 5.0 domains including EDM04, APO09, DSS02, MEA01. The result of this research is that the overall maturity level of RSIA Hamami is still at level 3. In the EDM04 domain, the maturity level obtained is 3.54. In the APO09 domain, the maturity level obtained is 3.48. In the DSS02 domain, the maturity level obtained was 3.20. In the MEA01 domain, the maturity level obtained is 3.24. From the results of the evaluation obtained, it can make RSIA Hamami more focused on improving the performance of the use of information system resources on the part that needs special attention. Through the COBIT 5.0 method, RSIA Hamami can see which parts of the hospital are still less than optimal, so that they can further develop and be able to provide the best service for patients in accordance with the vision and mission of RSIA Hamami.